2010
DOI: 10.1007/s11999-009-1032-2
|View full text |Cite
|
Sign up to set email alerts
|

Volar Percutaneous Screw Fixation for Scaphoid Waist Delayed Union

Abstract: Volar percutaneous cannulated screw fixation of acute scaphoid waist fractures reportedly produces high rates of healing and early return to work, but the method has not been reported for treating scaphoid waist delayed unions. We therefore report the surgical results of percutaneous screw fixation in scaphoid waist delayed union in 12 patients. All patients were male with an average age of 31.1 years. Duration of injury was 12 weeks (range, 6-20 weeks). However, no patient had carpal instability, scaphoid def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 29 publications
1
18
1
7
Order By: Relevance
“…Lastly, we do not agree with Kim and Lee [22] that percutaneous treatment should be used only in cases of delayed consolidation. We prefer to carry out screw fixation immediately, according to patients' age and working status.…”
Section: Discussioncontrasting
confidence: 56%
“…Lastly, we do not agree with Kim and Lee [22] that percutaneous treatment should be used only in cases of delayed consolidation. We prefer to carry out screw fixation immediately, according to patients' age and working status.…”
Section: Discussioncontrasting
confidence: 56%
“…All 15 fractures healed with the average time to union of 14 weeks with no complications. Kim et al [3] treated 12 patients with scaphoid waist delayed union using the volar percutaneous approach. All fractures united successfully with no additional procedures in an average 11 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous screw fixation has been advocated for minimally displaced acute scaphoid fractures and was recently reported for displaced scaphoid fractures [1,5]. A few reports have described the percutaneous approach for treating scaphoid delayed unions and non-unions [3,10]. This technique avoids devascularization of the scaphoid, division of the carpal ligaments, and providing a much more aesthetic scar [10].…”
Section: Introductionmentioning
confidence: 99%
“…These eventually healed without bone grafting. Other authors have suggested that selected nonunions may heal with rigid fixation alone, [15][16][17][18] and Kim, Kim and Lee 19 recorded union with slight resorption at the fracture site in 12 patients with delayed union of the waist of the scaphoid treated by percutaneous screw fixation.…”
Section: Discussionmentioning
confidence: 99%